Analysis of the n-GaN electrochemical etching process and its mechanism in oxalic acid. Issue 8 (7th February 2022) - Shushanian, Artem; Iida, Daisuke; Zhuang, Zhe; Han, Yu; Ohkawa, Kazuhiro
Abstract : We studied the mechanism of wet electrochemical etching of n-GaN films in oxalic acid. Abstract : We studied the wet electrochemical etching of n-GaN films in oxalic acid. The electrooxidation processes occur in a potentiostatic mode in the voltage range of 5 to 20 V. We described the formation of the porous n-GaN layer structures in several ways. Firstly, we observed the microphotographs of the cross section to characterize the nanostructure. Secondly, we examined the reaction products in a liquid phase using ICP-OES and TOC-TN methods, while vapor-phase products were examined by gas chromatography. Finally, according to the product data analysis, we demonstrate a mechanism for the electrochemical oxidation of n-GaN in oxalic acid, which involves 6 electrons.